PENGARUH PEMBERIAN EKSTRAK MENGKUDU (Morinda citrifolia L.) âFREEZE JUICINGâ TERHADAP KADAR GLUKOSA DARAH TIKUS WISTAR DIABETES MELLITUS - , MEITA ROCHMAWANGI, Prof. Dr. Ir. Y. Marsono, MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Diabetes mellitus (DM), a degenerative disease, is a metabolic disorder characterized by high levels of glucose in the blood. The prevalence of diabetes continues to rise and will be a serious health problem. Noni is an alternative functional foods that have hypoglycemic effects. Noni has a pungent odor and unpleasant. Freeze juicing extraction method is an alternative to the simple extraction to minimize the lack of it. Objective: This study aimed to determine the effect of noni extract \"freeze juicing\" on blood glucose levels wistar rats with diabetes mellitus. Method: The type of this research was a quasi experimental study with a type of design form, pre and post test control group design. Subject of this study is thirty Wistar rats aged 2 months and weighs about 160-180 grams. Rats were divided into 5 groups: negative control, positive control, freeze juicing noni doses of 0.25, 0.50 doses, and 1 dose during 28 days of treatment. Rats were adapted for 3 days, then fasted rats before induction of nicotinamide 110 mg and 45 mg streptozotocin. Analysis of blood glucose level was as much as 2 times (pre and post test). Data were analyzed using ANOVA. The results: Wistar rats was induced by streptozotocin and nicotinamide had increase blood glucose levels by an average blood glucose> 200 mg / dl. Statistical tests were conducted to determine the changes in blood glucose levels from pre-test to post test showed no significant difference between groups with p> 0.05. Juicing freeze noni extract had no effect on blood glucose levels decrease DM Wistar rats. Although the 0.5 dose group but decreased in the positive control group also decreased. Conclusions: Freeze juicing noni extract had no effect on blood glucose levels in Wistar rats with diabetes mellitus.